1977
DOI: 10.1016/0009-2614(77)80517-4
|View full text |Cite
|
Sign up to set email alerts
|

The extent of energy randomization in the infrared multiphoton dissociation of SF6

Abstract: Crossed laser and molecular beams were used to obtain the recoilenergy distribution of fragments in the study of multiphoton dissociation of SF 6. An average dissociation lifetime of-100 nsec was estimated from the laser pulse width dependence of the dissociation product. The results are in good agreement with the theoretical prediction of the RRKM model for unimolecular dissociation assuming an average excitation of-16 kcal per molecule beyond the dissociation threshold and complete energy randomization in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…218'253'254 This was used in Ref. 218, for example, to prove that in the case of SF6 first an atom of F breaks away and then the dissociation of the SF5 radical gives rise to the SF4 radical. The alternative dissociation mechanism SF6 SF4 + F2 was rejected since there were no F2 molecules detected.…”
Section: Overexcitation Of Polyatomic Molecules In Continuummentioning
confidence: 99%
“…218'253'254 This was used in Ref. 218, for example, to prove that in the case of SF6 first an atom of F breaks away and then the dissociation of the SF5 radical gives rise to the SF4 radical. The alternative dissociation mechanism SF6 SF4 + F2 was rejected since there were no F2 molecules detected.…”
Section: Overexcitation Of Polyatomic Molecules In Continuummentioning
confidence: 99%
“…1 1 In particular, statistical theory predicts that for simple bond rupture reactions where no exit barrier exists, the probability distribution for translational energy release, or P(ET), should be a monotonically decreasing function of translational energy peaking toward zero and overall releasing only a small fraction of the available energy as translation. 7 ' 8 In the case of molecular elimination channels, very often the presence of substantial exit barriers due to repulsion between the closed-shell products causes a larger amount of energy to go into translation and the P(ET) may peak away from zero. The observation of such translational energy distributions has been taken as -2-evidence of exit barriers in the potential energy surface.…”
Section: Introductionmentioning
confidence: 99%
“…When coupled with the infrared fluorescence detection technique described in Section II, dissociation by the uy excimer laser provides a versatile method for the study of H atom reactions. Although the details of the excitation need not concern us here, it will be of importance to note that several investigations (15)(16)(17)(18) have shown the SFg dissociation to be statistical in nature. The fragment energy distribution between the internal and translational degrees of freedom is accurately predicted by the RRKM theory of unimolecular reaction.…”
Section: Reactions Of Hydrogen Atomsmentioning
confidence: 98%
“…The fragment energy distribution between the internal and translational degrees of freedom is accurately predicted by the RRKM theory of unimolecular reaction. An elegant molecular beam technique (15) has shown that the products of multiphoton dissociation of SF6 recoil with very little translational energy. Two other investigations have demonstrated that the F atom dissociation fragment reacts with H2 at a rate which is similar to (iIpt, k r the reaction of thermal F atoms with H2.…”
Section: Reactions Of F Atoms With Hydrogen Halidesmentioning
confidence: 99%